Academic Atmosphere, Personality, and Academic Performance - Rini Nurahaju; Windah Riskasari (Yayasan Keluarga Guru Mandiri, 2023)
Academic performance is important in college. Therefore performance appraisal is carried out on lecturers and students who contribute to academic activities. This study aims to analyze academic performance in terms of academic atmosphere and personality. The latent variables used are academic performance as an endogenous variable and academic atmosphere and personality as exogenous variables. The type of research used is explanatory research, which aims to explain the influence between variables through hypothesis testing. The data collection technique uses a Likert scale: the academic atmosphere scale contains 24 items, and the personality scale contains 30 items. As for academic performance, it is revealed through student GPA and lecturer IKD. This research was carried out from June to July 2021 with 163 students and 37 lecturers at University X in Indonesia. The data analysis technique used SEM with the AMOS program. The results of the study resulted in the finding that there is a significant and positive effect of the Academic Atmosphere on Academic Performance. Furthermore, personality has a significant effect on academic performance.